(untitled) - Ohmae, Kenichi (Homewood, 1987)
Offers Americans an inside view of the Japanese business world by challenging Japanese businesses to reassess their position and responsibilities in the world of international trade
Keywords: International economic relations,Japan,Nhật Bản,Quan hệ kinh tế quốc tế; Foreign economic relations,Quan hệ kinh tế quốc tế; United states,Hoa Kỳ